2018
DOI: 10.5455/ijlr.20170611115020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Moringa oleifera Seed Meal on Nutrient Digestibility of Finisher Broiler Chickens

Abstract: This study was conducted to evaluate the effect of Moringa oleifera seed meal on nutrient digestibility of finisher broiler chickens. A total of 150

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…There were significant (p<0.05) differences in average final weight gain, average daily weight gain, average daily feed intake and feed conversion ratio with treatment 2 (toasted seed meal) showing the highest average final body weight of 2470 g when compared to with the rest of the trial diets, with treatment 4 having the least final weight of 1990 g in Table 2. This is consistent with previous reports [14][15][16] . The depressed weights recorded for the leaf meal fraction could be a result of the highly fibrous nature of the leaf meal which also resulted in a lower average daily feed intake.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…There were significant (p<0.05) differences in average final weight gain, average daily weight gain, average daily feed intake and feed conversion ratio with treatment 2 (toasted seed meal) showing the highest average final body weight of 2470 g when compared to with the rest of the trial diets, with treatment 4 having the least final weight of 1990 g in Table 2. This is consistent with previous reports [14][15][16] . The depressed weights recorded for the leaf meal fraction could be a result of the highly fibrous nature of the leaf meal which also resulted in a lower average daily feed intake.…”
Section: Resultssupporting
confidence: 94%
“…However, this contrasts sharply with the previous report by Anyanwu et al 2 which recorded a significant reduction in the feed intake and weight gains among birds fed diets containing Moringa oleifera and Pueraria phaseoloides leaf meals. Abdulkarim et al 15 also reported increased digestibility in dry matter digestibility in broiler finisher birds.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation